Pneumothorax leading to pneumopericardium after transvenous lead implantation in a patient with previous epicardial lead. Issue 3 (18th December 2020) - Bansal, Raghav; Mahajan, Ankit; Rathi, Chetan; Lokhandwala, Yash
Abstract: A 44‐year‐old lady, a follow‐up case of idiopathic dilated cardiomyopathy and cardiac resynchronization therapy defibrillator device implantation with epicardial left ventricular (LV) lead, underwent a transvenous LV lead revision in view of epicardial lead malfunction. A chest X‐ray after this, done for worsening dyspnea, revealed pneumopericardium along with left pneumothorax. The computed tomography (CT) revealed a communication between the left pleural and pericardial cavities, around the old epicardial lead. Drainage of the left pleural cavity resolved both the pneumothorax and pneumopericardium and the patient remained well on follow up.